Study on the effectiveness of coir fibre geo-textile for erosion control under the dynamic approach - Mazlan, Maizura; Abu Eusuf, Muhammad; Hj. Baharuddin, Zainul Mukrim; Othman, Rashidi (2008)
This paper presents the effectiveness of coir geotextiles for erosion control. In the context of sustainable slope management, coir is a cheap and locally available material that can be used to strengthen traditional earthen bunds or protect the banks of river from erosion. Particularly in developing countries, where coir is abundantly available and textiles can be produced by small-scale industry, this is an attractive alternative for conventional methods